Darcy-Forchheimer MHD micropolar water based hybrid nanofluid flow, heat and mass transfer features past on stretching/shrinking surface with slip and radiation effects - Memon, M. Asif; Jacob, Kavikumar; Bux Lanjwani, Hazoor; Mahmoud, Emad E. (elsevier, 2024)
Hybrid nanofluids (HNF) play a vital role in enhancing the heat transfer characteristics of all types of traditional fluids, both in industrial and experimental applications. In this regard, the laminar two-dimensional (2D) boundary layer magnetohydrodynamic (MHD) Darcy-Forchheimer flow, heat transfer, and mass transfers characteristics of Cu–MoS2/micropolar water-based hybrid nanofluid have been considered over a stretching/shrinking surface. The thermal radiation and partial slip effects are considered in a porous medium. The governing partial differential equations (PDEs) are transformed into ordinary differential equations (ODEs) using appropriate similarity transformations. The equations are numerically solved using the shooting method in Maple software, and dual solutions are obtained for different ranges of the applied parameters. The effects of the different physical parameters and nanoparticle volume fractions on velocity, microrotation, temperature, and concentration profiles along with skin friction, couple stress, Nusselt and Sherwood numbers are examined. The main findings of this study show that the velocity profiles decrease with an increase in the suction, the Darcy-Forchheimer number, velocity slip, magnetic and micromaterial parameters, while oppositely, it increases with an increase in nanoparticle volume fractions. Moreover, an increase in the magnetic field, nanoparticle volume fractions, and thermal radiation increases the temperature profiles, while an increase in the Prandtl number, suction, and thermal slip parameters decreases it. An increase in nanoparticle volume fractions decreases skin friction, the couple stress coefficient, and the Nusselt number, but increases the Sherwood number with the variation of suction.